Parallel imports and manufacturer rebates: Evidence from Germany - Laura Birg (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
In this paper, I study the effect of a change in the mandatory manufacturer rebate on wholesale prices for pharmaceuticals on competition by parallel imports. First, I analyze the effect of a manufacturer rebate on competition by parallel imports in a two-country model. An increase in the manufacturer rebate increases the market share of parallel imports. Second, I exploit a policy reform in Germany in 2010 that increased the manufacturer rebate by 10 percentage points. Using a data set with prescription drugs with competition from parallel imports, I estimate the effect of the change in the manufacturer rebate on competition by parallel imports. Estimation results suggest that an increase in the manufacturer rebate has increased the market share of parallel imports.
Keywords: F12; I11; I18; 330; parallel imports; manufacturer rebate; pharmaceuticals; regulation